Conjunctival extramedullary plasmacytoma: a case study and literature review - Yun-Feng XU; Ming YAN (Yixue xinzhi zazhi)
Extramedullary plasmacytoma (EMP) is a rare type of plasmacytoma characterized by the abnormal proliferation of plasma cells. It can be divided into primary and secondary types according to the cause and often occurs in the head and neck, while conjunctival EMP usually develops in the form of primary EMP. At present, domestic and foreign research on conjunctival EMP is relatively rare. This article reports a case of conjunctival EMP in a 43-year-old man. The patient had only limited lesions in the extramedullary conjuncti-va, and the tumor was visible in the conjunctiva and bulbar conjunctiva of the right eyelid. This article reports the treatment process and prognosis of this patient and reviews the related literature on conjunctival EMP, aim-ing to provide a reference for its correct diagnosis and treatment.